2020
DOI: 10.2141/jpsa.0190078
|View full text |Cite
|
Sign up to set email alerts
|

Verification of the Effectiveness of an SNP Marker in the Cholecystokinin Type A Receptor Gene for Improving Growth Traits in Okumino-kojidori Chickens

Abstract: sA significant association was reported between a single nucleotide polymorphism (SNP; AB604331, g. 420 C > A) in the cholecystokinin type A receptor gene and growth traits in some Japanese slow-growing chickens. Demonstration tests of the genetic improvement effect by comparing the superior allele-A fixed chickens with conventional ones were carried out considering the effect of different seasons on growth traits in other slow-growing chickens. Meat-type Okumino-kojidori chickens from Gifu Prefecture are a th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…For example, in the distal region of chromosome 4 where CCKAR is located, the CCKAR SNPs— other than g.420 C>A ( Dunn et al , 2013 ) and the SNPs in other candidate genes ( Lyu et al , 2017 )—have been suggested to affect growth traits by studies on resource populations of White Leghorn×commercial broilers ( Dunn et al , 2013 ) and New Hampshire×White Leghorn ( Lyu et al , 2017 ), respectively. Regardless, without doubt, the g.420 C>A SNP is a quality marker for marker-assisted selection to improve growth traits with a wide application range in chickens, since a significant association is reported between the SNP and growth traits in other commercial slow-growing chickens (Amakusa Daioh cross chicken, Takahashi et al , 2019 ; Miyazaki Jitokko chicken, Horinouchi et al , 2019 ; Hinai-jidori chicken, Rikimaru et al , 2019 ; Okuminokojidori chicken, Ishikawa et al , 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in the distal region of chromosome 4 where CCKAR is located, the CCKAR SNPs— other than g.420 C>A ( Dunn et al , 2013 ) and the SNPs in other candidate genes ( Lyu et al , 2017 )—have been suggested to affect growth traits by studies on resource populations of White Leghorn×commercial broilers ( Dunn et al , 2013 ) and New Hampshire×White Leghorn ( Lyu et al , 2017 ), respectively. Regardless, without doubt, the g.420 C>A SNP is a quality marker for marker-assisted selection to improve growth traits with a wide application range in chickens, since a significant association is reported between the SNP and growth traits in other commercial slow-growing chickens (Amakusa Daioh cross chicken, Takahashi et al , 2019 ; Miyazaki Jitokko chicken, Horinouchi et al , 2019 ; Hinai-jidori chicken, Rikimaru et al , 2019 ; Okuminokojidori chicken, Ishikawa et al , 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The National Agriculture and Food Research Organization (NARO) and the Akita Prefectural Livestock Experiment Station have reported that a SNP site (AB604331, g.420 C>A in DDBJ; rs313822901 in NCBI dbSNP) in the 5 ′ -untranslated region of the cholecystokinin type A receptor gene ( CCKAR ) is associated with growth traits in the Hinai-dori breed of the Akita Prefecture in Honshu, Japan (Rikimaru et al , 2013). The effectiveness of the g.420 C>A SNP as a selection marker for improved growth traits has been investigated in other commercial slow-growing chickens (Amakusa Daioh cross chicken, Takahashi et al , 2019 ; Miyazaki Jitokko chicken, Horinouchi et al , 2019 ; Hinaijidori chicken, Rikimaru et al , 2019 ; Okumino-kojidori chicken, Ishikawa et al , 2020 ). These studies conclude that the A allele of the g.420 C>A SNP is superior for improving growth traits.…”
Section: Introductionmentioning
confidence: 99%